Sexual behaviour among male methamphetamine and heroin dependents attending drug rehabilitation clinic / Mohd Fadzli Mohamad Isa - Mohd Fadzli , Mohamad Isa (2012)
The debates about associations between drugs use and sex have been going on for decades. Drugs use and sex are mediums of pleasure and bring about sense of euphoria and enjoyment. Illicit drugs use has evolved from natural-based drugs such as opiates and cannabis to synthetic-based substances such as amphetamine and methamphetamine. This evolution even modifies the motives of drug use from just a primary emotion-altering substance that cut the users on the loose into a substance that can increase enthusiasm, motivation and self-esteem. The effect of methamphetamine on sociability and emotional loosening effects of heroin has increased their use in social functions and also sexual activities. However, how far methamphetamine and heroin is used for sexual acts in a relatively conservative country like Malaysia is uncertain. Aim The aim of this study is to describe the pattern of sexual behaviour among users of the two most commonly used drugs in Malaysia currently. Malaysian methamphetamine and heroin users, who live in community-setting and are predominantly males and heterosexuals, may reveal another perspective with regards of their drug use and sexual behaviour. Unlike several previous studies, this current study aims to describe the pattern of sexual behaviour not only based on risky sexual behaviour, but other aspects of sex such as desire, interest, iii drive and obsession in relation to the drug use. It is hoped that the results of this study can be utilized to improve the current drug treatment and rehabilitation programme which does not so much emphasize on sexual behaviour. Methodology A cross-sectional study was carried out in three Malaysian cities: Kota Kinabalu, Kota Bharu and Kuala Lumpur which are well-known to have high numbers of methamphetamine and heroin users. The subjects were all living in the community and have satisfactory psychosocial functioning. This study was primarily based on a validated sexual behaviour self-rated questionnaire followed by a brief face-to-face interview. Results A total of 227 subjects were included in this study with 124 (54.6%) were using methamphetamine while 103 (45.4%) were using heroin. Majority (218; 96%) of the participants were heterosexuals with 104 (45.8%) reported having been involved in high risk sexual behaviour. More methamphetamine than heroin subjects agreed that their sexual thoughts, feelings and behaviours were often associated with the drug (p<0.05). Methamphetamine subjects agreed that the use of methamphetamine caused them to be more obsessed with sex and they found themselves to be preoccupied with sexual thoughts while being under the influence of the drug (p<0.05). Heroin subjects mainly reported on negative effects of the drug on their sexual behaviour. Methamphetamine subjects reported that the use of drug had positively affected their sexual interest and drive (Adjusted OR = 1.050; p<0.05). iv Methamphetamine subjects were also 1.97 times more likely than heroin subjects to be involved in risky sexual behaviour. Conclusions Methamphetamine subjects reported positive effect of the drug on one sexual domain which is sexual interest, drive and pre-occupation while heroin subjects reported many negative effects of the drug on sex. Methamphetamine subjects were more likely than heroin subjects to be involved in risky sexual behaviour.